(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article discusses the use, possibilitics and organization of pedagogical diagnostics in primary education. It also reflects the views of students on the diagnosis of cognitive development through computer technology.